Well-Being and Teaching Effectiveness of Primary School Teachers - Mathew, Smitha; N, Vasuki (THE PRIMARY TEACHER, 2019)
Teachers who are in good mental health can create an upbeat and friendly atmosphere at school to stop students from having mental health issues and make sure they feel like they belong. How teachers feel psychologically and how happy they are with their job impact how they act. The study attempts to determine the relationship between well-being and teacher effectiveness among primary school teachers in Kerala. For this study, a sample of 200 primary school teachers was selected using simple random sampling. The psychological well-being scale (PWBS) constructed by Dr. Devendera Singh Sisodia and Ms. Pooja Chaudhary (2012) and the Teacher Effectiveness scale by Kumar and Mutha (2017) adopted by the investigator were used for the study. Data analysis revealed a significant positive relationship between the components of psychological well-being and teacher effectiveness among primary school teachers in Kerala.